Recurrent orbital cellulitis secondary to the ‘forgotten’ scleral buckle: a case report - Hor, SM; Noor Aniah A,; Mushawiahti Mustapha,; Malisa A,; Mae-Lynn Catherine Bastion, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Scleral buckle placement is a well-established technique for the treatment of primary rhegmatogenous retinal detachment. Complications associated with scleral buckle are uncommon and its presentations can be vary. We report a case of recurrent orbital cellulitis with anterior segment ischemia following a forgotten episode of previous scleral buckling surgery, presenting with blurring of vision, redness and swelling of the lids. The presence of scleral buckle was detected by detailed examination and confirmed by orbital imaging. Orbital infection and rubeosis iridis were successfully treated with scleral buckle removal, intravenous antibiotics and intracameral ranibizumab. However, the retinal detachment recurred and the visual acuity deteriorated to light perception. There was no further intervention as the family declined in view of her old age. In cases of recurrent orbital infection, detailed clinical examination is important to look for evidence of ocular prostheses as a source of infection. Orbital imaging is an adjunct for making the diagnosis especially in cases where history is unreliable. Anterior segment ischemia due to scleral buckle responds well to buckle removal with ranibizumab injection.